2016
DOI: 10.1016/j.jacc.2016.05.092
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C and Cardiovascular Disease

Abstract: BACKGROUNDEpidemiological studies show that high circulating cystatin C is associated with risk of cardiovascular disease (CVD), independent of creatinine-based renal function measurements. It is unclear whether this relationship is causal, arises from residual confounding, and/or is a consequence of reverse causation.OBJECTIVESThe aim of this study was to use Mendelian randomization to investigate whether cystatin C is causally related to CVD in the general population.METHODSWe incorporated participant data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(40 citation statements)
references
References 46 publications
0
38
0
Order By: Relevance
“…Further, those indices have no causality with regard to atherosclerotic events. 62 , 63 Therefore, it might be inappropriate to undertake statistical analysis upon eGFR and cystatin C as independent determinants for baPWV, because we hypothesize that baPWV is a prognostic predictor. Fourth, we excluded some patients as possible ASO patients using not only borderline ABI (≤0.99) but also by using high %MAP (≥45) and UT (≥180).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, those indices have no causality with regard to atherosclerotic events. 62 , 63 Therefore, it might be inappropriate to undertake statistical analysis upon eGFR and cystatin C as independent determinants for baPWV, because we hypothesize that baPWV is a prognostic predictor. Fourth, we excluded some patients as possible ASO patients using not only borderline ABI (≤0.99) but also by using high %MAP (≥45) and UT (≥180).…”
Section: Limitationsmentioning
confidence: 99%
“…It is not the case that chronic kidney disease, or end-stage renal failure alone can predict a poorer prognosis. 2 , 61 Nevertheless, recent Mendelian randomization studies have, at least, cast doubt on the causative relationship between cardiovascular prognosis and eGFR or cystatin C. Specifically, causative factors related to eGFR and CAD 62 and on the association between serum cystatin C and cardiovascular events 63 are evaluated. In other words, these studies potentially suggest that the surrogate indices of renal function, such as eGFR and serum cystatin C, are only mediating factors of prognosis.…”
Section: Limitationsmentioning
confidence: 99%
“…Cystatin C is well established in the assessment of renal function and nephropathy in T1DM, but recent interest has centred on its potential value in cardiovascular risk assessment [ 60 ]. Epidemiological studies show a strong association between circulating cystatin C and the development of CVD independent of renal function [ 61 ]. Serum uromodulin appears to have renal protective properties; higher levels also appear to be associated with reduced coronary artery calcification [ 62 ].…”
Section: Candidate Biomarkers Of Cardiovascular Riskmentioning
confidence: 99%
“…At least partially, some studies have recently shed light on this topic. First, based on the fact that several single nucleotide polymorphisms are associated with circulating cystatin C level [22,23], prospective observational studies [24,25] and mendelian randomization studies [10,11] have shown that high levels of cystatin C are not causally related to the incidence of coronary artery disease, ischemic stroke, and heart failure. In particular, mendelian randomization studies rely on a very large sample size and on the fact that genetic information, randomly distributed from parents to offspring, are not influenced by either disease status (reverse causality) or potential confounders.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, since elastolytic cysteine proteases and their inhibitors are involved in the pathogenesis of atherosclerosis, it has also been suggested that cystatin C levels may be directly linked to the development and progression of atherosclerosis [8,9]. However, mendelian randomization studies [10,11] have shown that the association between cystatin C and cardiovascular disease is not causal. Nonetheless, its role as a marker of atherosclerosis (reverse causality) is still controversial.…”
Section: Introductionmentioning
confidence: 99%